(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Coal mining is negatively impacting the environment as a whole. On the fragile world, the chaotic human race is continually utilizing a range of tools for everyday life. Coal has been known as India’s primary source of electricity for many decades and leads to about 27 per cent of the world’s industrial energy requirements. Coal is primarily extracted using two types, surface or opencast, and underground mines. The process of mining is dictated by the geological environment. Coal mining is generally correlated with the depletion of environmental wealth and ecosystem loss. This allows invasive species to inhabit the region, posing a danger to biodiversity. A variety of mining operations in the coal mining area create large amounts of waste material. Mining can harm the natural ecosystem if due consideration is not taken for the handling of waste. The waste management system impacts ground, water and climate and, in effect, the quality of life of residents in surrounding regions. This paper focuses on the pressing problems of coal mining and their effect on the ecosystem.